The Longitudinal Study Of Medical And Health Care Studentsâ€™ Experiences And Attitudes Towards Interprofessional Learning In First Semester Course - Tervaskanto-Maentausta, Tiina; Nordstrom, Tanja; Varkki, Essi; Taanila, Anja (European Scientific Journal, ESJ, 2016)
Interprofessional course â€œPublic health and interprofessional collaborationâ€ was planned for the first semester medical and health care students by two universities of Oulu, Finland. The course architecture was built on blended methods including lectures, video based workshops, interactive e-learning phase based on family cases with everyday health and wellbeing problems of the family members. The course ended with student conference. All together 1681 students from ten different degree programs participated in the course during the years 2007-2013. In this paper we describe the studentsâ€™ readiness and attitudes towards interprofessional learning (IPL) with RIPLS (Readiness towards interprofessional learning scale) in the beginning of the course and studentsâ€™ feedback and learning experiences at the end of the course using the web based inquiry. The attitudes and readiness towards IPL were evaluated quite positive. The highest RIPLS scores were evaluated in Teamwork and collaboration. The different development of the attitudes between the groups was seen in Roles and responsibilities. In the longitudinal perspective the medical students evaluated all of the subscales lower than the health care students. The scoring stayed in the same level during the years. The difference between the groups was significant. The learning outcomes correlated linearly with studentsâ€™ own activity. Those students, who took actively part in web and group discussions learned most. Family cases helped them to get the big picture of the service system. Based on students feedback participative methods gradually replaced the traditionally methods like lectures during the years. The learning outcomes were evaluated relatively good.